Assessment of Patients’ Adherence to Antiepileptic Medications at Dessie Referral Hospital, Chronic Follow-Up, South Wollo, Amhara Region, North East Ethiopia - Gizachew Kassahun; Getachew Moges; Yitayew Demessie (Neurology Research International)
An epileptic seizure is a clinical event presumed to result from an abnormal and excessive neuronal discharge. The clinical symptoms are paroxysmal and may include impaired consciousness and motor, sensory, autonomic, or psychic events perceived by the subject or an observer. Epilepsy occurs when 2 or more epileptic seizures occur unprovoked by any immediately identifiable cause. And in the majority of patients with epilepsy, antiepileptic drugs effectively control their illness. However, more than 30% of people with epilepsy do not attain full seizure control, even with the best available treatment regimen. The aim of this study is to assess self-reported adherence in adult patients with epilepsy and to identify potential barriers for nonadherence to antiepileptic drug treatment in Dessie Referral Hospital. A hospital based cross-sectional study was conducted using structured questionnaires including Morisky medication adherence scale and analysis was conducted descriptively using SPSS version 20. The level of nonadherence to antiepileptic medication regimens was 34.1%. The major reason for missing medication was forgetfulness 53.5%. And the most common side effect was sedation 56.2%. Conclusion. Majority of epileptic patients in Dessie Referral Hospital was adherent to their AEDs treatment and among the determinants of adherence assessed the level of education and the side effect of drugs showed statistical significance.